2023
DOI: 10.55131/jphd/2023/210106
|View full text |Cite
|
Sign up to set email alerts
|

Levels and risk factors associated with depression, anxiety, and stress among COVID-19 infected adults after hospital discharge in a Southern Province of Thailand

Abstract: The long-term effects on the mental health of people living with COVID-19 are emerging as a global threat to public health. This study aimed to determine the levels and risk factors associated with depression, anxiety and stress (DAS) among COVID-19 infected adults discharged from a hospital in a high-risk area in Thailand. A cross-sectional study was performed with 512 participants aged 18 years and above who had been infected with COVID-19 and discharged between 3 and 12 months in Hat Yai District, Songkhla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…While sociodemographic and COVID-related details did not prove essential for the optimal machine learning models detecting depression, anxiety, and stress in recovered COVID-19 patients, their inclusion exhibited high accuracies (all > 0.700). This observation, portrayed through the number of features and accuracy in the depression, anxiety, and stress datasets, suggests that sociodemographic information and COVID-19-related details may indeed influence the mental well-being of recovered COVID-19 patients, aligning with findings from other studies [28,[36][37][38].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While sociodemographic and COVID-related details did not prove essential for the optimal machine learning models detecting depression, anxiety, and stress in recovered COVID-19 patients, their inclusion exhibited high accuracies (all > 0.700). This observation, portrayed through the number of features and accuracy in the depression, anxiety, and stress datasets, suggests that sociodemographic information and COVID-19-related details may indeed influence the mental well-being of recovered COVID-19 patients, aligning with findings from other studies [28,[36][37][38].…”
Section: Discussionsupporting
confidence: 83%
“…In terms of disease conditions, our results highlighted associations between depression, anxiety, and stress with underlying diseases, such as non-communicable diseases, hypertension, diabetes, heart disease, and respiratory disease. This aligns with existing research emphasizing that underlying diseases are significant risk factors contributing to the severity of symptoms related to depression, anxiety, and stress [36][37][38], underscoring the need for heightened mental health awareness, particularly among those with underlying health issues.…”
Section: Discussionsupporting
confidence: 75%
“…The COVID-19 pandemic continues to affect communities worldwide, with post-COVID conditions emerging as a significant concern, particularly mental health issues. Prior research conducted in Thailand has demonstrated high levels of depression, anxiety, and stress among COVID-19 patients [ 18 , 35 ]. However, our study observed a lower prevalence of significant mental health problems among most COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…From January to April 2023, the total number of cases was recorded at around 5,000 [ 17 ]. A recent report conducted in Thailand indicated that the majority of respondents experienced depression, anxiety, and stress (>87.7%) among recovered COVID-19 patients during the pandemic [ 18 ]. Despite several recent studies on long COVID and mental health disorders, these were primarily review papers that relied on highly heterogeneous studies encompassing different questionnaires, time points, countries, and age groups [ 19 ], or were based on hospitalized individuals [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dense population of the city, combined with the varying availability of urban green space across its districts, provides a valuable opportunity to investigate the potential mental health benefits of green space access during a period of unprecedented stress and disruption ( 12 ). On March 26, 2020, Bangkok implemented strong public health and social measures, including a full-scale city lockdown, curfews, and mandatory face masks, including the closure of places such as parks and recreational centers ( 13 ). The importance of urban green space visitation has increased with the closure of parks and public spaces.…”
Section: Introductionmentioning
confidence: 99%